2020
DOI: 10.1111/1462-2920.14906
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA coaR contributes to intestinal colonization in Vibrio cholerae via the two‐component system EnvZ/OmpR

Abstract: Vibrio cholerae is a waterborne bacterium responsible for worldwide outbreaks of acute and fatal cholera. Recently, small regulatory RNAs (sRNAs) have become increasingly recognized as important regulators of virulence gene expression in response to environmental signals. In this study, we determined that two-component system EnvZ/OmpR was required for intestinal colonization in V. cholerae O1 EI Tor strain E12382. Analysis of the characteristics of OmpR revealed a potential binding site in the intergenic regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…We note that there are conflicting reports regarding the contribution of ompR to intestinal colonization, suggesting that there may be strain differences among V. cholerae isolates. A recent study reported that ompR was required for colonization (65), while three other studies suggested that ompR was dispensable for colonization (66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…We note that there are conflicting reports regarding the contribution of ompR to intestinal colonization, suggesting that there may be strain differences among V. cholerae isolates. A recent study reported that ompR was required for colonization (65), while three other studies suggested that ompR was dispensable for colonization (66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…Red thick arrows with flat cap indicate inhibition. References: Hammer and Bassler, 2007;Jang et al, 2011;Cobaxin et al, 2014;Mey et al, 2015;Ng et al, 2016;Dorman and Dorman, 2018;Jemielita et al, 2018;Butz et al, 2019;Xi et al, 2020. with RA, a group of sRNAs showed differential expression in response to the presence of RA, including the induction of RsmY (Fernández et al, 2018). This study highlights the relevance of sRNAs in the communication process between host and pathogen.…”
Section: Infectious Diseases In Plantsmentioning
confidence: 73%
“…Very interestingly, it is not directly the environmental cue that triggers alterations in the expression level of the sRNA, but the mRNA levels of the target gene, mtlA. Another sRNA recently described, CoaR, binds to the mRNA of tcpI to block its translation (Xi et al, 2020; Figure 7). TcpI is a negative regulator of tcpA, a gene encoding the structural major pilin subunit of TCP (Harkey et al, 1994).…”
Section: Nutritional Immunitymentioning
confidence: 99%
“…CoaR targets the tcpI gene encoding the negative regulator of the major pilin subunit TcpA, which is important for host colonization. Accordingly, the deletion of this sRNA negatively impacts the colonization of the small intestine of mice [ 58 , 59 ].…”
Section: Srnas Regulating Host-pathogen Interactionsmentioning
confidence: 99%